Hasil Belajar dan Kinerja Siswa SMA pada Pembelajaran Konsep Protista Melalui Pendekatan Inquiri Terbimbing - Fathul Zannah (Anterior Jurnal, 2013)
Learning activities in SMAN 2 Banjarbaru has led to the observation of activities, but not optimal guided inquiry approach in detail. This resulted in performance students have not been honed, which is indispensable in biology education. This study aims to: test the significance of student learning outcomes in the form of a product between treatment classes and control classes, test the significance of the process of student learning outcomes between treatment classes and control classes, measure student performance. The study was designed with a quasi-experimental The Nonequivalent Control Group Design. Sample of this study is class grade students X5 and X4 as a class treatment and X1 as a control classes. There are differences of the average of learning product treatment classes with control classes in 3 times learning (29.5 to 28.21; 51.2 to 28.93; 70.2 to 27.14). This difference was significant sequential (Fo = 16.76, P = 0.0001, Fo = 43.60, P = 0.0001, Fo = 140.47, P = 0.0001), there are differences in the average learning in the class of treatment with a class of learning control in 3 times learning (53.8 to 30.36; 60 to 37.5: 72.1 to 31.43). This difference was significant sequential (Fo = 88.77, P = 0.0001, Fo = 98.76, P = 0.0001, Fo = 245.92, P = 0.0001, the performance of students, characterized by behavioral skills, social and psychomotor skills assessment has increased.